Getting to zero : Australia's energy transition - Finkel, Alan (Carlton, VIC : Black Inc., an imprint of Schwartz Books, 2021)
An essential guide to how Australia can tackle climate crisis The world is overheating, and despite good intentions and significant efforts, emissions increase nearly every year. The challenge is immense, but there are solutions. In this lucid, inspiring essay, Alan Finkel maps Australia's path forward. He explains the solar and wind revolution, and addresses the challenge of intermittent supply. He introduces hydrogen, the energy hope of the future. He traces the rise and rise of the electric car. He shows how we can build a zero-emissions world. Taking into account economics, science and emotions, Getting to Zero is an essential guide to how Australia can tackle the climate crisis with realism and ingenuity.
Title from cover.
Includes bibliographical references.
Keywords: Ecology; Hybrid electric vehicles; Politics and government; Renewable energy sources; Solar energy industries; Wind power; Solar energy industries -- Australia; Wind power -- Australia; Hybrid electric vehicles; Climatic changes -- Prevention -- Technological innovations; Global warming -- Prevention; Waste gases -- Environmental aspects; Renewable energy sources -- Australia; Australia; Australia -- Politics and government; Australia -- Environmental conditions; Australian